Brief case : pitfalls of planning. - GOOLD, Michael (1990)
Notes that despite its high promise, strategic planning frequently makes little contribution to improving a company's performance. For various reasons, the strategic plan fails to alter directions that have already been set or takes the company down the wrong path, or is simply ignored by the line managers. Focuses on one cause for this state of affairs: 'never addressed the real issues'.